THE ELEVENTH GRADE STUDENTS’ ABILITY IN USING DEMONSTRATIVE PRONOUNS AT SMA SWASTA BINA GUNA TANAH JAWA SIANTAR IN THE ACADEMIC YEAR OF 2021/2022 - Purba, Elina; Tarigan, Karisma Erikson; Ginting, Fiber Yun Almanda (Kairos English Language Teaching Journal, 2022)
This study aims to determine whether students are able to use demonstrative pronouns at SMA Bina Guna Tanah Jawa Siantar. This study uses a multiple choice test design with 40 questions. The froblem of this study is the student’s ability to use demonstrative pronouns. To answer the formulation of the problem related to the research objectives, the writer applies a quantitative method, namely giving tests to students and formulated in multiple choice items. Data collected through post-test consists of 34 students. The writer uses the total sample technique in this study. It means that all samples in the class are taken. The date results show that there are a total of 32% of all students’ answers which can be classified as low and have not reached the minimum score, and the average score of students is 3.0 which means the category is low and students’ weaknesses in using pointing pronouns are in those because they only get 23%, the weaknesses obtained with the thesis were 25%, followed by 42%, and finally there were those who got 47%, the writer concludes that the weakness of using demonstrative pronouns is in those. Based on the findings and discussion, the researcher concluded that the students’ ability to use the demonstrative pronoun method was low at SMA Bina Guna Tanah Jawa Siantar.